Special formulas involving polygonal numbers and Horadam numbers - Adegoke, K.; Frontczak, R.; Goy, T. (Carpathian Mathematical Publications, 2021)
Some convolution-type identities involving polygonal numbers and Horadam numbers are derived. The method of proof is to properly relate the generating functions to each other. Additionally, we prove a general non-convolutional result involving these number families and discuss some of the consequences.